2009
DOI: 10.3389/neuro.10.027.2009
|View full text |Cite
|
Sign up to set email alerts
|

Multiquantal release underlies the distribution of synaptic efficacies in the neocortex

Abstract: Inter-pyramidal synaptic connections are characterized by a wide range of EPSP amplitudes. Although repeatedly observed at different brain regions and across layers, little is known about the synaptic characteristics that contribute to this wide range. In particular, the range could potentially be accounted for by differences in all three parameters of the quantal model of synaptic transmission, i.e. the number of release sites, release probability and quantal size. Here, we present a rigorous statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 51 publications
(108 reference statements)
7
99
2
Order By: Relevance
“…One study reported MVR at L2/3 neurons in V1 at room temperature (Watanabe et al, 2005), which was in contrast with other reports in S1 (Rozov et al, 2001;Koester and Johnston, 2005). Another recent study suggested that MVR occurred at L5 synapses in S1 (Loebel et al, 2009). Here, our data provide strong evidence in favor of MVR at RS-RS connections of L4 in S1 under physiological conditions based on the differential block of Kyn, which clearly indicates that the local glutamate transient changes during the train.…”
Section: Multivesicular Release At Cortical Synapsescontrasting
confidence: 56%
“…One study reported MVR at L2/3 neurons in V1 at room temperature (Watanabe et al, 2005), which was in contrast with other reports in S1 (Rozov et al, 2001;Koester and Johnston, 2005). Another recent study suggested that MVR occurred at L5 synapses in S1 (Loebel et al, 2009). Here, our data provide strong evidence in favor of MVR at RS-RS connections of L4 in S1 under physiological conditions based on the differential block of Kyn, which clearly indicates that the local glutamate transient changes during the train.…”
Section: Multivesicular Release At Cortical Synapsescontrasting
confidence: 56%
“…Our model assumes that each synaptic contact hosts exactly one vesicle docking site, in contrast to similar models in which a single contact can dock multiple vesicles (Vere-Jones 1966;Wang 1999;de la Rocha and Parga 2005;Loebel et al 2009). This difference could potentially be resolved by interpreting our parameter M as the total number of release sites at all contacts, but this resolution is only consistent if vesicle release at each site is statistically independent.…”
Section: Discussionmentioning
confidence: 99%
“…Initial applications relied on conducting experiments under a variety of conditions, in particular varying the extracellular Ca 2+ concentration to alter the vesicle release probability (Foster and Regehr, 2004; Birò et al, 2005). Brémaud et al (2007) and Loebel et al (2009) increased the practicality of the method by using short-term vesicle depletion to vary the effective release probability under a single experimental condition. Their analyses showed that multiquantal release underlies the wide range of EPSP amplitudes observed (Song et al, 2005; Lefort et al, 2009) and that, in general, it is not the case that the number of distinct anatomical contacts equals the maximum number of readily-releasable vesicles as was put forward by the single-vesicle hypothesis (Kuno, 1971; Korn et al, 1981).…”
Section: Introductionmentioning
confidence: 99%